Clinical Supervision in Primary Education within Islamic Educational Perspectives: A Contemporary Literature Review on Mentoring, Reflective Practice, and Teacher Professional Development - Merita Diana; Samsul Hadi; Wahyu Febriana; Binti Luthfiah; Nirva Diana; Agus Paharudin (ISTAWA, 2025)
This literature review examines the evolving role of clinical supervision in strengthening instructional quality and teacher professional development within primary education. Drawing on peer-reviewed articles, books, and empirical reports published between 2020 and 2025, the review synthesizes contemporary perspectives on supervisory models, mentoring practices, reflective processes, and the integration of digital technologies. Using an interpretive qualitative approach, the analysis identifies four major themes: (1) a shift from directive, compliance-based supervision toward collaborative and dialogic models; (2) the expanding role of mentoring as a relational support system that enhances novice teachers’ confidence, identity formation, and pedagogical competence; (3) reflective practice as a central mechanism enabling teachers to analyze instructional decisions, interpret student learning, and improve adaptability; and (4) the growing influence of digital tools such as video observations, online feedback platforms, and virtual mentoring communities in facilitating accessible, evidence-based supervisory interactions. The findings highlight that effective clinical supervision emerges when mentoring, reflective dialogue, and digital mediation function synergistically to support continuous teacher growth. However, challenges remain, including uneven digital literacy, limited cross-contextual evidence, and the absence of integrated frameworks connecting these developmental elements. This review calls for context-responsive, technology-enhanced, and conceptually unified models of clinical supervision that better align with the complex instructional demands of primary education.